2008
DOI: 10.1007/s00405-008-0761-2
|View full text |Cite
|
Sign up to set email alerts
|

Association of laryngopharyngeal manifestations and gatroesophageal reflux

Abstract: The aim of this study was to investigate the prevalence of gastroesophageal reflux disease (GERD) in patients with laryngopharyngeal symptoms, the relationship between laryngopharyngeal reflux (LPR) and Helicobacter Pylori infection and treatment response to proton pump inhibitors. Forty-five patients with suspected gastroesophageal reflux diseases related symptoms (sore throat, throat burning, throat clearing, globus sensation, cough, halitozis, dysphonia, dysphagia, postnasal dripping, vocal fatigue, and spu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
39
1
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 16 publications
8
39
1
6
Order By: Relevance
“…Several studies on LPR have found globus pharyngeus as the most common symptom, while some studies have found other symptoms of LPR more common like throat burning, hoarseness, cough. [7][8][9][10][11] In our study most common symptom of LPR was found to be frequent clearing of throat in 98%, which was similar in the study by Toros et al 12 Other common symptoms seen in our study were sensation of lump in throat and troublesome cough in 96% of patients each. Dyspnoea/choking (38%) was least common symptom seen our patients.…”
Section: Discussionsupporting
confidence: 88%
“…Several studies on LPR have found globus pharyngeus as the most common symptom, while some studies have found other symptoms of LPR more common like throat burning, hoarseness, cough. [7][8][9][10][11] In our study most common symptom of LPR was found to be frequent clearing of throat in 98%, which was similar in the study by Toros et al 12 Other common symptoms seen in our study were sensation of lump in throat and troublesome cough in 96% of patients each. Dyspnoea/choking (38%) was least common symptom seen our patients.…”
Section: Discussionsupporting
confidence: 88%
“…Öksürüğün oluşma mekanizması, enflamatuvar proçeslerin öksürük refleksini oluşturan duyu sinirlerini stimüle etmesiyle ilişkilidir. [2,12] Astımda epizodik wheezing, nefes darlığı, göğüste sıkışma hissi, öksürük gibi semptomlar ve dinlemekle ronküsler vardır. Solunum fonksiyon testlerinde (SFT) reversibl havayolu obstrüksiyonu varsa veya metakolin inhalasyonu ile yapılan bronkoprovokasyon testi pozitif ise astım tanısı konur.…”
Section: Discussionunclassified
“…[12] Larengeal muayenede LFR bulguları olan hastalarda ampirik proton pompa inhibitörü kullanımının klinik bulguları etkin bir şekilde önlediğini bildiren yayınlar vardır. [13] Belafsky ve ark.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Wynik ten jest niŜszy od podawanych w literaturze. Toros podaje, Ŝe zaczerwienienie nalewek występowało u prawie 80% pacjentów [143]. Obrzęk błony śluzowej tylnego odcinka krtani widoczny był u wszystkich przebadanych chorych, z czego nieco ponad połowa miała obrzęk łagodny a pozostali bar-dziej nasilone zmiany obrzękowe w krtani.…”
Section: Omówienieunclassified